Integrating digital and conventional recording techniques for the documentation and reconstruction of an 18th-Century wooden ship from Alexandria, VA. (March 2020) - Grieco, Glenn; Fix, Peter; Kennedy, Carolyn; Herbst, Julia; Shultz, Lauren; Borrero, Ricardo; Dostal, Christopher
Abstract: An 18th-century wooden ship discovered on the waterfront of Alexandria, Virginia was documented and modelled using laser scanning, computer modelling, 3D printing, traditional lines drawings, and wooden ship modelling techniques. This combination of new technologies and traditional ship documentation methods allowed researchers to capture the details of the ship remains with extremely high accuracy. The models of the timbers were then 3D printed, reassembled, and incorporated into an interpretive wire frame model that contextualized the remains of the ship with what it would have looked like whole.